Program Evaluation through Handwashing with Soap in COVID-19 Prevention at Garuda Health Center Pekanbaru: Evaluasi Program melalui Cuci Tangan Pakai Sabun (CTPS) dalam Pencegahan COVID-19 di Puskesmas Garuda Pekanbaru - Astri Khoir K (JOURNAL OF MEDICAL AND HEALTH SCIENCE, 2024)
The importance of handwashing with soap (CTPS) behavior during the COVID-19 pandemic plays a significant role in preventing the transmission of infectious diseases. However, document reviews and interviews at Garuda Health Center in Pekanbaru City indicate that the achievement of CTPS is still low, at only 29%. This low achievement is caused by a lack of cross-program coordination between environmental health program holders and health promotion, as well as the non-implementation of Community-Based Total Sanitation (STBM) triggering activities in 2020 due to the COVID-19 pandemic. This study aims to evaluate the implementation of the Clean and Healthy Life Behavior (PHBS) program through CTPS activities in efforts to prevent COVID-19 at Garuda Health Center in Pekanbaru City, and to formulate alternative problem-solving strategies through the development of an intervention plan (Plan of Action). This study uses a qualitative method with data collection techniques in the form of in-depth interviews, field observations, and document reviews regarding the implementation of the STBM program. The research informants consist of the Head of the Community Health Center (Puskesmas), the Head of Administration, the holder of the STBM program, and related staff. The results of the study show that the achievement of CTPS is still low due to weak cross-program coordination and suboptimal community empowerment activities. Improvement efforts are carried out by preparing a work plan (RUK) and a Plan of Action in the form of strengthening cross-program coordination, training environmental health workers, providing health promotion media, and improving CTPS facilities in public places. It is concluded that the evaluation of the PHBS program through CTPS needs to be focused on strengthening cross-sector collaboration to improve clean and healthy living behaviors of the community in the working area of Garuda Community Health Center, Pekanbaru City.